Unjuk Kerja Turbin Angin Sumbu Horizontal Berdiaemeter 2,6 Meter Di Gedung C Fakultas Teknik Universitas Riau - Tino Ferinando GS; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Electrical energy needs are increasing and limited fossil energy triggers a rapid development in renewable energy. One of the renewable energy resources is wind turbines. The kinetic energy of the wind can be converted into electrical energy using wind turbines. The purpose of this study is to figure out  the performance of horizontal axis wind turbines with 5 inverse taper type blades. Wind turbines located at a height of 19 m above the ground. The power output of generator was measured  with load conditions. The load was given for this testing is 10 Ohm Resistor. Data collected from the testing were wind speeds, electrical voltages and rotational speeds. From the test achieved maximum of 49,24 Watt when the wind speed of 8,3 m/s. Wind turbine generator starts generate electrical power at a wind speed of 2  m/s. The maximum achievement of power coefficient of 0,0369  at TSR 0.721.   Keywords: Wind turbine, wind speed, electrical voltage, rotational speed, power coefficient